Blood glucose may be another index to initiate insulin treatment besides glycated hemoglobin A1c after oral antidiabetic medications failure for glycemic control: A real–world survey - Li, Yanli; Wu, Yan; Shu, Yi; Li, Shu; Pei, Jianhao; Chen, Hong; Liu, Shiping; Xiang, Guangda; Wang, Wenbo; Shan, Pengfei; Su, Heng; Wu, Xiaoyan; et al. (Frontiers in Endocrinology, 2022)
Objective: The inertia of insulin initiation is a barrier to achieving glycemic control when oral antidiabetic drugs fail to control glucose during the treatment of type 2 diabetes （T2D）. Insulin initiation is usually based on glycated hemoglobin A1c (A1C). To investigate whether there is another index for insulin initiation besides A1C，we conducted a cross-sectional survey in the real world. Methods: We conducted a multicenter cross-section survey with a total of 1034 T2D patients. All patients, at the time of the survey, decided to initiate insulin therapy due to failure of controlling glucose using only oral antidiabetic drugs. We analyzed the differences of blood glucosebetween patients who were tested for A1C and those who were not. Results: 666 (64.4%) patients were tested A1C and 368 (35.6%) were not. Neither fasting blood glucose (FBG) (12.0 ± 2.9 vs 12.3 ± 2.9 mmol/L, t = 1.494, P = 0.135) nor postprandial blood glucose (PBG) (18.4 ± 4.8 vs 17.9 ± 4.8 mmol/L, t = 1.315, P = 0.189) were significantly different between patients with and without A1C. Conclusion: This survey indicated that initiating insulin based on FBG and PBG does exist in clinical practice. Though there are no difference between patients with and without A1C, FBG and PBG have been far higher than guideline recommended target, so we still suggest that blood glucose may be another index when deciding whether to initiate insulin therapy.